c - STILTON, GERONIMO (New York Scholastic, Inc, 2013)
In Thea Stilton and the Legend of the Fire Flowers (Book #15), the Thea Sisters travel to Hawaii for a prestigious international hula competition. While facing rivalry from the Ruby Crew, they discover that a nearby volcano, Mauna Loa, is set to erupt, forcing them to use their skills to save everyone in time.
English